Academic libraries and toxic leadership - Ortega, Alma C. (Cambridge, MA, United States Chandos Publishing, an imprint of Elsevier, 2017)
Academic Libraries and Toxic Leadership examines a phenomenon that has yet to be seriously explored. While other professions, such as nursing, have been studies for their tendency to create toxic leadership environments, thus far academic librarianship has not. This book focuses on how to identify a toxic leader in an academic library setting, how to address toxic leadership, and how to work toward eradicating it from the organization. In addition, the author discusses actions to take to prevent libraries from hiring toxic leaders. -- Back cover.
Includes bibliographical references and index.
Keywords: Academic libraries -- Management; Leadership; Organizational behavior; Academic libraries -- Management; Leadership; Organizational behavior